KEPUTUSAN PEMERINTAH INDONESIA UNTUK BERGABUNG DALAM ASIAN INFRASTRUCTURE INVESTMENT BANK (AIIB) - Arif Miftakhudin (HI 16 UMY 112, 2016)
*112 This thesis aims to analyse why Indonesia Government Decision to Join Asian Infrastructure Investment Bank (AIIB). The thesis found that the reasons of Indonesian Government to join AIIB caused by consideration of domestic political aspect, economic matters, and aspect of international context matters. The policy of the president Joko Widodo about the main priority of state development, economic capability problem that indicate insufficient fund to develop infrastructure investment, also China’s policy of One Belt One Road. Those are the consideration of Indonesian government on deciding to join AIIB. The establishment of AIIB aims to increase connectivity in Asia through infrastructure development which caused Indonesian Government to consider becoming a member state of AIIB. Keyword: Asian Infrastructure Investment Bank (AIIB), Indonesian Government, Decision, Consideration